2012
DOI: 10.1038/ki.2012.193
|View full text |Cite
|
Sign up to set email alerts
|

The serum 24,25-dihydroxyvitamin D concentration, a marker of vitamin D catabolism, is reduced in chronic kidney disease

Abstract: Chronic kidney disease is characterized, in part, as a state of decreased production of 1,25-dihydroxyvitamin D (1,25(OH)2D); however, this paradigm overlooks the role of vitamin D catabolism. We developed a mass spectrometric assay to quantify serum concentration of 24,25-dihydroxyvitamin D (24,25(OH)2D), the first metabolic product of 25-hydroxyvitamin D (25(OH)D) by CYP24A1, and determined its clinical correlates and associated outcomes among 278 participants with chronic kidney disease in the Seattle Kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
133
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(145 citation statements)
references
References 45 publications
(38 reference statements)
9
133
0
3
Order By: Relevance
“…Similar to prior cross-sectional studies in CKD cohorts (15,16,26,27), our investigation demonstrated lower baseline 24,25(OH) 2 D 3 concentrations in patients with CKD, as well as a positive correlation between eGFR and baseline 24,25 (OH) 2 D 3 concentrations (Supplemental Figure 2). The lack of statistical significance between baseline 24,25(OH) 2 D 3 concentrations in the CKD and control groups was not unexpected because our power calculations were based on the anticipated variability in post-treatment 25(OH)D 3 concentrations and not differences in baseline 24,25(OH) 2 D 3 concentrations.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Similar to prior cross-sectional studies in CKD cohorts (15,16,26,27), our investigation demonstrated lower baseline 24,25(OH) 2 D 3 concentrations in patients with CKD, as well as a positive correlation between eGFR and baseline 24,25 (OH) 2 D 3 concentrations (Supplemental Figure 2). The lack of statistical significance between baseline 24,25(OH) 2 D 3 concentrations in the CKD and control groups was not unexpected because our power calculations were based on the anticipated variability in post-treatment 25(OH)D 3 concentrations and not differences in baseline 24,25(OH) 2 D 3 concentrations.…”
Section: Discussionsupporting
confidence: 74%
“…However, no clinical trials have prospectively tested this hypothesis. Furthermore, crosssectional data from humans and rodent models of CKD suggest that 24,25(OH) 2 D concentrations are lower in the setting of impaired kidney function (13,(15)(16)(17)26). Given the apparent disparity between these clinical observations and current theories regarding vitamin D metabolism in CKD, further in vivo investigation of the 24-hydroxylase pathway can provide valuable insight into the pathophysiology of mineral metabolism derangements in CKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies conducted so far were crosssectional and hence subject to temporality bias. In fact, the product of 25(OH)D metabolism (24,25[OH]D) seems to be decreased in CKD, leading to a stagnating metabolism of vitamin D (11). Thus, the level of 25(OH)D could paradoxically be higher among people with early stages of CKD than among those with adequate eGFR (11).…”
Section: Introductionmentioning
confidence: 97%
“…In fact, the product of 25(OH)D metabolism (24,25[OH]D) seems to be decreased in CKD, leading to a stagnating metabolism of vitamin D (11). Thus, the level of 25(OH)D could paradoxically be higher among people with early stages of CKD than among those with adequate eGFR (11). The 1,25(OH) 2 D deficiency in CKD could be mediated via fibroblast growth factor-23 (FGF-23), a protein that is elevated in CKD and inhibits the conversions of 25(OH)D into 1,25(OH) 2 D and stimulates the catabolism of 1,25(OH) 2 D (12,13).…”
Section: Introductionmentioning
confidence: 99%